Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage Terhadap Audit Delay - Karel Miroslav Jacob Vieira; Ayu Aulia Oktaviani (Ikatan Da'i Indonesia, 2026)
This think about points to look at the impact of benefit, firm estimate, and use on review delay in genuine bequest and property companies recorded on the Indonesia Stock Exchange (IDX) during the period 2022–2024. Convenient budgetary detailing is basic for keeping up the significance and unwavering quality of bookkeeping data, whereas review delay may decrease the convenience of money related explanations for partners. This investigate utilized a quantitative approach utilizing auxiliary information gotten from yearly reports and examined monetary explanations. The test was chosen employing a purposive inspecting strategy, and the information were analyzed utilizing board information relapse with EViews. The results indicate that productivity incorporates a negative impact on review delay, proposing that companies with higher profitability tend to total the review handle more rapidly. Firm estimate moreover incorporates a negative impact on review delay since bigger companies for the most part have way better inside control frameworks and detailing capabilities. In the interim, use incorporates a positive impact on review delay due to the expanded complexity and review chance related with higher obligation levels. These discoveries give suggestions for company administration, evaluators, speculators, and controllers in progressing the convenience of money related announcing.